Determinasi Pertumbuhan Ekonomi Indonesia dalam Sudut Pandang Moneter - Pathi Farhan, Muhammad; Desmintari, Desmintari; Nani Ariani, MB (Jurnal Indonesia Sosial Sains, 2022)
Sustainable economic growth towards a better condition over a certain period is a goal that every developed and developing country wants to achieve, including Indonesia. Many indicators affect economic growth in Indonesia, such as investment, exchange rates and interest rates. This study aims to determine the effect of investment, exchange rates and interest rates on economic growth in Indonesia. The research method used in this research is time series data regression analysis and quantitative descriptive analysis supported by existing quantitative data. The results of this study indicate that investment has no effect on economic growth, while the exchange rate, and both exchange rates and interest rates affect economic growth. Investment has no effect on economic growth because Indonesia's investment is still only focused on the industrial and agricultural sectors so that it does not have a significant effect on economic growth. There is an influence between the exchange rate on Indonesia's economic growth due to the stability of the rupiah which is an indicator to show the strength of the Indonesian currency in front of the world.